Fracture resistance, two point bending strength and morphological characteristics of pulpless teeth restored with fiber-reinforced composite posts - Betsy Kilian Martins Luiz; Fabiana Paladini Mattei; Karoliny Remor Moreira Francisco; Marcelo Carvalho Chain; Alfredo Tibúrcio Nunes Pires (Revista Sul-Brasileira de Odontologia, 2013)
Fiber-reinforced composite posts (FRC posts) have been used for tooth reinforcement after endodontic treatment. The mechanical characteristics of FRC posts can influence the clinical prognostic. Objective: The aim of this study was to evaluate the flexural strength and fracture resistance of commercially available FRC posts Material and methods: Fourteen human single-rooted premolars with completely formed apices were selected and received endodontic treatment. The specimens were divided into two groups related to the post system: i) Group A – cylindrical-conical fiberreinforced post (White post DC, FGM), and ii) group B – conical fiber-reinforced post (EXACTO, Angelus). The fracture resistance was evaluated and two point bending tests were carried out. The glass fiber characteristics and the tag penetration of the luting material into the radicular dentin structure were evaluated through scanning electronic microscopy in an illustrative way. One-way ANOVA and Tukey’s HSD test (α = 0.05) were applied. Results: The values obtained for fracture resistance and two point bending test were, respectively, 399.29 N and 109.5 N for group A, and 386.25 N and 119.5 N for group B. No significant differences in strength values among the groups were found. Conclusion: There were no significant statistical differences between the two post groups regarding to fracture strength and two point bending strength. It can be concluded that the posts selected for this study performed satisfactorily in terms of mechanical properties so that they can be used for tooth reinforcement after endodontic treatment.